Development of a dried blood spot HPLC‐PDA method for the analysis of linezolid and ciprofloxacin in hospital‐acquired pneumonia patients. Issue 10 (12th May 2017) - Ferrone, Vincenzo; Carlucci, Maura; Cotellese, Roberto; Raimondi, Paolo; Cichella, Annadomenica; Di Marco, Lorenzo; Genovese, Salvatore; Carlucci, Giuseppe
Abstract : This study developed a high performance liquid chromatography (HPLC) method involving dried blood spotting (DBS) as a sampling method for the therapeutic drug monitoring of antimicrobial combination therapy with linezolid and ciprofloxacin. DBS for standards, quality control samples, and patient samples was excised and then extracted using a mixture of methanol/water/formic acid 80:20:0.1 ( v/v/v ), respectively. Linezolid (LZD) and ciprofloxacin (CPR) were measured by HPLC using a Kinetex EVO C18 (100 × 4.6 mm I.D. 2.6 μm particle size). Mobile phase consisted of 10 mM ammonium acetate (A) and a mixture of acetonitrile and methanol (B), both containing 0.1% triethylamine, in gradient elution. Detection was carried out at 251 nm for linezolid (LZD) and 277 for ciprofloxacin (CPR). Ulifloxacin was used as an internal standard. The internal standard, LZD, and CPR were eluted in 7.90, 7.18, and 8.89 min, respectively. Total run‐time was 20 min. Calibration curves were constructed in the range of 0.05–30 μg/mL for LZD and 0.02–10 μg/mL for CPR, respectively. The intra‐ and inter‐day precision (RSD values) did not exceed 9.43%, the intra‐ and inter‐day accuracy (accuracy %) ranged between 96.2 and 106.2%. Haematocrit (Hct) effects were investigated to obtain a linear correlation between haematocrit values and volume of blood. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Development of a dried blood spot technique as an easy tool for the therapeutic drug monitoring of linezolid and cirprofloxacin in patients with hospital acquired pneumonia (HAP).